(untitled) (Journal of Plant Disease Sciences, 2021)
Turmeric rhizome rot disease is one of the major constraints to turmeric cultivation throughout India. Turmeric cultivation has increased in the Western Maharashtra zone due to favourable climatic conditions. However, floods in the Western Maharashtra zone cause massive losses in the turmeric crop due to rhizome rot disease. Considering the yield losses caused by rhizome rot disease, the investigation was planned to assess the effect of rhizome size on rhizome rot disease caused by Pythium aphanidermatum. The result revealed that, rhizome seed weight of 10g had the lowest germination count (43.52%) and the highest disease incidence (63.48%). Whereas rhizome seed weight of 70g was the found to be superior in increasing the germination percentage of 94.35% and recorded lowest disease incidence (6.51%) with maximum yield of 213 g per pot.